A muscle cell variant defective in glycosaminoglycan biosynthesis forms nerve-induced but not spontaneous clusters of the acetylcholine receptor and the 43 kDa protein - Gordon, H (J Neurosci, 1993)
Myotubes of the C2 mouse muscle cell line form clusters of ACh receptors (AChRs) at apparently random sites along their length when cultured alone, and near sites of nerve-muscle contact when cocultured with neurons. We find in aneural cultures that myotubes of a C2 variant, S27, which is defective in glycosaminoglycan synthesis, express the AChR on their surface, but do not form clusters. S27 cells in aneural cultures also express the 43 kDa protein but do not cluster it. The altered distribution of laminin and collagen IV on the surface of S27 myotubes suggests that the basal lamina is abnormal. Neither the addition of exogenous proteoglycans or conditioned medium from wild- type C2 cells, nor the growth of S27 cells on substrates rich in basal lamina elements caused clusters to appear on S27 myotubes in aneural cultures. When cultured with primary neurons, however, S27 myotubes formed large clusters of the AChR near sites of neurite contact. The clusters were coincident with patches of the 43 kDa protein. Prelabeling experiments indicate that at least some AChRs in the clusters arise through aggregation. Although Torpedo agrin induces AChR clusters on C2 myotubes, it does not do so on S27 cells. Our experiments suggest that the spontaneous formation of clusters of AChRs and the 43 kDa protein in aneural cultures of myotubes depends upon the normal synthesis of muscle proteoglycans, and that nerve-induced clustering does not. Thus, there appear to be multiple mechanisms for the formation of AChR clusters.